2013
DOI: 10.2320/matertrans.m2013170
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical and Optical Properties of Fe–O–N Thin Films Deposited by RF Magnetron Sputtering

Abstract: The electrical and optical properties of FeON films were investigated in order to find their possibilities for solar cell application. FeON thin films were deposited on glass substrates by RF magnetron sputtering using an ArN 2 O 2 reactive gas. Under optimum flow rates of nitrogen and oxygen, the FeON films showed equivalent electrical properties to amorphous Si that has been conventionally used for thin film solar cells. Bandgap narrowing was also observed from 2.0 to 1.9 eV. The observed results were consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…2327) Recently, the present authors have reported on the electrical and optical properties of Fe-O-N films deposited by reactive RF magnetron sputtering under O 2 gas flow rate of 0.10.25 sccm and N 2 gas flow rate of 15 sccm. 28) It was found that the resistivity of the as-deposited films increased from 10 2 to over 10 6 ³ cm with increasing the oxygen gas flow rate. Moreover, the resistivity was found to decrease by more than 3 orders after annealing at 673 K. Such changes in the resistivity of the films may be due to the change of crystal structure of the films, but was not clear.…”
Section: Introductionmentioning
confidence: 99%
“…2327) Recently, the present authors have reported on the electrical and optical properties of Fe-O-N films deposited by reactive RF magnetron sputtering under O 2 gas flow rate of 0.10.25 sccm and N 2 gas flow rate of 15 sccm. 28) It was found that the resistivity of the as-deposited films increased from 10 2 to over 10 6 ³ cm with increasing the oxygen gas flow rate. Moreover, the resistivity was found to decrease by more than 3 orders after annealing at 673 K. Such changes in the resistivity of the films may be due to the change of crystal structure of the films, but was not clear.…”
Section: Introductionmentioning
confidence: 99%
“…A close look into Figure 8 shows that the reduction of oxygen partial pressure in the process leads to the decrease in the band gap. The energy gap of the magnetite film reported in the literature is 0.1 eV [11] or 0.3 eV [43], whereas it is higher for maghemite thin film. Optical properties of maghemite thin film were not studied in detail in the literature but the expected value of its direct optical band gap is larger than 2.46 eV [44].…”
Section: Optical Propertiesmentioning
confidence: 82%
“…The interest in the study of 2 of 15 iron oxynitride films (Fe-O-N) is to elaborate a material that exhibits intermediate properties between those of iron oxide and iron nitride films. The Fe-O-N thin films have been studied for potential application to photoelectrochemical water splitting to generate hydrogen, solar application [11], magnetic [12], optical, electronic, etc. properties [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, neither of these forms of iron oxide are known to have the combination of low resistivity and high mobility values measured here. Fe 3 O 4 is reported to have resistivity of the order of 10 3  Ω-cm2021 while it is of the order of 10 3  Ω-cm for γ -Fe 2 O 3 22. A 41 nm thickness epitaxial magnetite film has been reported to have an effective hall mobility of about 0.07 cm 2 /V-s with a maximum anomalous hall mobility of 35 cm 2 /V-s23.…”
Section: Discussionmentioning
confidence: 99%